Critical Thinking Ability As A Correlate Of Senior Secondary School Students’ Achievement In Physics In Sokoto State, Nigeria - Afees Akanni Amuda; Esther O. Omosewo; Ridwan Enuwa Mohammed (IJER (Indonesian Journal of Educational Research), 2022)
This paper examined critical thinking as a correlate of students’ achievement in physics in Sokoto State, Nigeria. This study adopted ex post facto research of the co-relational type. The population for the study was Senior Secondary School II (S.S.S. II) students in Sokoto State. The sample consisted of 731 S.S.S. II offering physics proportionately selected from Senior Secondary Schools across the three senatorial districts in Sokoto State, Nigeria. Research instruments employed to elicit data for the study were the Critical Thinking Inventory (SCTI), and Physics Achievement Test (PAT). The instruments were validated by experts in science education and physics giving reliability coefficients 0.86 and 0.76 respectively. The data gathered were analysed using Pearson Product Moment Correlation Coefficients (PPMC) and Fishers-z transformation (Z-test) statistic at .05 level of significance. The findings of the study revealed that: there was a statistically significant relationship between students’ critical thinking ability and their achievement in physics (r = 0.23, p < .05); there was no statistically significant difference in the strength of the relationship between students’ critical thinking ability and their achievement in physics in favour of female students; and there was a statistically significant difference in the strength of the relationship between critical thinking ability and physics achievement in favour of public schools. It was recommended that students should be trained on how to think critically to be able to predict correctly their achievement in physics.